LncRNA‐encoded pep‐AP attenuates the pentose phosphate pathway and sensitizes colorectal cancer cells to Oxaliplatin. (15th November 2021) - Wang, Xinyi; Zhang, Haiyang; Yin, Shengjie; Yang, Yuchong; Yang, Haiou; Yang, Jiayu; Zhou, Zhengyang; Li, Shuang; Ying, Guoguang; Ba, Yi
Abstract: Oxaliplatin (L‐OHP) is a standard treatment for colorectal cancer (CRC), but chemoresistance is a considerable challenge. L‐OHP shows dose‐dependent toxicity, and potential approaches that sensitize cancer cells to L‐OHP could reduce the dosage. With the development of translatomics, it was found that some lncRNAs encode short peptides. Here, we use ribosome footprint profiling combined with lncRNA‐Seq to screen 12 lncRNAs with coding potential, of which lnc‐AP encodes the short peptide pep‐AP, for their role in L‐OHP resistance. Co‐IP and LC‐MS/MS data show that the TALDO1 protein interacts with pep‐AP and that pep‐AP suppresses the expression of TALDO1. The pep‐AP/TALDO1 pathway attenuates the pentose phosphate pathway (PPP), reducing NADPH/NADP + and glutathione (GSH) levels and causing ROS accumulation and apoptosis, which sensitizes CRC cells to L‐OHP in vitro and in vivo . pep‐AP thus might become a potential anticancer peptide for future treatments of L‐OHP‐resistant CRC. Synopsis: lncRNA‐encoded pep‐AP sensitizes tumor cells to L‐OHP, represses the pentose phosphate pathway and induces redox imbalance, which has potential therapeutic implications for the treatment of L‐OHP‐resistant colorectal cancer. Ribo‐seq identifies lnc‐AP as a lncRNA that correlates with L‐OHP resistance. lnc‐AP‐encoded pep‐AP interacts with TALDO1, promotes cell apoptosis, and increases cellular sensitivity to L‐OHP in colorectal cancer. Abstract : lncRNA‐encoded pep‐AP sensitizes tumor cells to L‐OHP, represses the pentose phosphate pathway and induces redox imbalance, which has potential therapeutic implications for the treatment of L‐OHP‐resistant colorectal cancer.